THEORETICAL FOUNDATIONS OF BLENDED LEARNING TECHNOLOGY AND ITS SIGNIFICANCE IN THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2025)
This article discusses blended learning as a modern pedagogical approach that integrates traditional face-to-face education with online and digital technologies. This approach enhances the learning process by offering students flexibility, opportunities for independent study, and access to interactive tools. Research findings highlight that blended learning effectively combines teaching methods and models, boosting student engagement and motivation. Within this system, students actively participate in the learning process, choose methods suited to their needs, and access diverse resources. Key advantages of blended learning include virtual classrooms, online assessments, and flexible schedules. Enriched with innovative technologies, blended learning plays a crucial role in modern education systems, contributing to improved educational outcomes.